Impact of the Application of Domestic Wastewater by Subsurface Drip Irrigation on the Soil Solution in Sugarcane Cultivation - Aline Azevedo Nazário; Ivo Zution Gonçalves; Eduardo Augusto Agnellos Barbosa; Leonardo Nazário Silva dos Santos; Daniel Rodrigues Cavalcante Feitosa; Edson Eiji Matsura (Applied and Environmental Soil Science)
The agricultural use of domestic sewage is a viable alternative for recycling nutrients; however, there is concern regarding the impact of its use due to the concentration of chemical elements present in this type of effluent. The use of principal component analysis determines the existence or lack of anomalous samples and the relations between measured variables and their relative contribution among samples that help in monitoring the impact of the use of effluents on soil chemical components. Thus, the objective of this work was to identify nutrient ions present in the soil solution during the first ratoon sugarcane irrigated with treated domestic sewage applied by subsurface drip irrigation. The experiment was conducted under a randomized block design with 5 treatments and 5 replicates. The treatments were distributed according to the type of water applied in the irrigation system (water surface reservoir and treated domestic sewage), the installation depth of the drip tapes (0.2 or 0.4 m depth), and the treatment without irrigation. By means of soil solution, it was possible to identify an increase in the concentration of salts in the treatments irrigated with treated domestic sewage, which however did not affect the soil quality in the short term. The principal component analysis selected the variables Ca2+, Mg2+, NO3−, K+, and EC as soil solution indicators to monitor areas irrigated with treated domestic sewage.